Formulasi Sediaan Shampoo Bar Ekstrak Daun Waru (Hibiscus tiliaceus L) dan Uji Aktivitas Antijamur terhadap Candida albicans - Amanah, Nur; Retno Sari, Dwi; Muhammad fauzi, Fawwaz (Universitas Borneo Lestari, 2026)
Sensitive, oily, or dandruff-prone scalp conditions can cause discomfort and negatively affect hair health. Candida albicans is an opportunistic fungus known to contribute to dandruff formation. Waru leaves (Hibiscus tiliaceus L.) contain various bioactive compounds, including saponins, flavonoids, polyphenols, and tannins, which are reported to have antifungal properties. This study aimed to analyze the active compounds of waru leaf extract, evaluate the physical stability of a shampoo bar formulation, and assess its antifungal activity against Candida albicans. This research employed an experimental design, with extraction carried out using maceration in 96% ethanol. The obtained extract was formulated into shampoo bars at concentrations of 3%, 6%, and 9%. The formulations were evaluated for organoleptic properties, pH, foam height, and foam stability. Antifungal activity was tested using the disc diffusion method against Candida albicans, with three replications. A commercial shampoo bar (“x”) was used as the positive control, while the base formulation without active ingredients served as the negative control. The results showed that all formulations met the physical evaluation criteria, except for pH values which exceeded the Indonesian National Standard (SNI). Antifungal testing revealed inhibition zones of 5.7 mm, 6.05 mm, and 6.85 mm for formulas I, II, and III, respectively, with the 9% formulation demonstrating the highest inhibitory activity against Candida albicans. In conclusion, waru leaf extract (Hibiscus tiliaceus L.) can be successfully formulated into a shampoo bar and exhibits antifungal activity against Candida albicans, with the 9% concentration showing the greatest effectiveness.